2022
DOI: 10.1371/journal.pcbi.1010666
|View full text |Cite
|
Sign up to set email alerts
|

How public can public goods be? Environmental context shapes the evolutionary ecology of partially private goods

Abstract: The production of costly public goods (as distinct from metabolic byproducts) has largely been understood through the realization that spatial structure can minimize losses to non-producing “cheaters” by allowing for the positive assortment of producers. In well-mixed systems, where positive assortment is not possible, the stable production of public goods has been proposed to depend on lineages that become indispensable as the sole producers of those goods while their neighbors lose production capacity throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
1
5
0
Order By: Relevance
“…found that bacteria living in more structured habitats encode more extracellular proteins with higher diffusibility. 74 These findings are consistent with the adaption of siderophore privatization proposed by our model and other works, 48 , 72 where the private portion is more advantageous in highly mixed environments.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…found that bacteria living in more structured habitats encode more extracellular proteins with higher diffusibility. 74 These findings are consistent with the adaption of siderophore privatization proposed by our model and other works, 48 , 72 where the private portion is more advantageous in highly mixed environments.…”
Section: Discussionsupporting
confidence: 92%
“… 48 The work of Lerch et al. discovered that when two public goods exist, a species producing a completely public good can exclude non-producers by partially privatizing another public good, 72 and this ability is highly reliant on nutrient supply, underscoring the significance of environmental conditions for sustaining cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased population viscosity (i.e., limited dispersal) has been shown to promote cooperation. 29 , 30 An increase in population viscosity makes the benefits of cooperation preferentially available to other cooperators by limiting the dispersal of the cooperators themselves, thus selecting for increased cooperation. 31 In contrast, a decrease in population viscosity spreads the benefits of cooperation to others regardless of their contribution.…”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms communicate and cooperate with each other to perform various activities, such as nutrient acquisition, biofilm formation, among other functions ( 1 4 ). Often, members of a microbial population produce extracellular resources, such as an enzyme or a metabolite, to achieve these functions ( 5 , 6 ). Since these products are released in the extracellular environment and both producers and non-producers enjoy the benefits of these secretions, they are referred to as public goods.…”
Section: Introductionmentioning
confidence: 99%